2020
DOI: 10.12890/2020_001832
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Enigma: Spindle Cell Sarcoma of the Aorta Presenting as Pulmonary Embolism and Chronic Anaemia

Abstract: Primary aortic sarcoma is a rare and aggressive malignancy with only approximately 190 cases reported in the literature. While angiosarcoma and intimal sarcomas represent an estimated 67.7% of malignant aortic tumours, spindle cell sarcomas are even more exclusive, consisting of only 0.9% of malignant aortic tumours. Differentiated from other malignant aortic tumours, spindle cell sarcomas are of mesenchymal origin and usually express vimentin and osteopontin. Clinical presentations are variable and nonspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Primary aortic tumors are extremely rare and frequently correspond with malignant mesenchymal tumors. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Few studies have been reported (<100 cases since 1998), with the latest a case series with a review of the literature by Böhner et al. 4 , 9 Because of its deep location, silent growth, and clinical and imaging findings that mimic thrombosis and atherosclerosis, its diagnosis can be difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary aortic tumors are extremely rare and frequently correspond with malignant mesenchymal tumors. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Few studies have been reported (<100 cases since 1998), with the latest a case series with a review of the literature by Böhner et al. 4 , 9 Because of its deep location, silent growth, and clinical and imaging findings that mimic thrombosis and atherosclerosis, its diagnosis can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that even metastatic aortic sarcomas can be controlled for some time with radiotherapy or chemotherapy (doxorubicin and ifosfamide) if the metastasis is limited, if the tumor is not resectable, and in embolic situations. 4 , 5 , 6 , 7 , 8 , 9 Even with adjuvant treatment, these entities have a very poor prognosis (worse with thoracic aortic involvement), with a median survival of 14 to 16 months. The cause of death for 80% of these patients is metastatic disease (ie, bones, kidneys, liver, adrenal glands, lungs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few reports of distant metastasis of LMS in the extremities. As for the distal embolization of sarcoma, there are reports of sarcoma of the aorta [13] , vena cava [14] , and heart [15] , causing pulmonary embolism at close range. More distantly, there have been reports of pulmonary embolism from renal sarcoma [16] and upper limb arterial embolization from aortic arch sarcoma [17] .…”
Section: Discussionmentioning
confidence: 99%